POLA DAN LOGIKA NIKAH SIRRI DALAM KULTUR MASYARAKAT MADURA - Faiz, Abd Aziz (Sunan Kalijaga State Islamic University & The Asia Foundation, 2013)
Sirri marriage does not seem to be a problem in Maduran society, even when the women are often harmed during or after the marriage. This apparent indifference can be explained by analyzing the cultural logic of Maduran society, among them through the patriarchal relations where women are ignorant of public administration issues, the view that women must be protected, herded and made into an asset of men’s pride. The paradigms regarding virginity (parabhan) and spinsters, and the fiqh-based religious reasoning apparent in Maduran society exacerbates the problem. There are several explanations for the patterns of sirri marriages in Madura: poverty, ignorance or lack of information on behalf of the women, the practice of arranged marriages (ajuduagi) and polygamy. Sirri marriages in Madura leads to child laborers supporting families, underage widows due to incapacity of handling domestic conflicts and hindrances for women from accessing their rights in many aspects due to their dependence on men.